2013
DOI: 10.1155/2013/132794
|View full text |Cite
|
Sign up to set email alerts
|

Silica-ZnCl2: An Efficient Catalyst for the Synthesis of 4-Methylcoumarins

Abstract: Silica-ZnCl2 has been found to be an efficient and eco-friendly catalyst for the synthesis of substituted 4-methylcoumarins from ethyl acetoacetate and substituted phenols under “neat” conditions in an oil bath at 80°C. The experimental procedure is simple, includes shorter reaction times (15–65 min), compatible with sensitive functional groups, and results in excellent yield of the products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…5). Further there is no weight loss upto 800 C. Therefore it can be concluded that physiosorbed and chemisorbed ZnBr 2 on silica surfaces is stable upto 800 C. 37…”
Section: Resultsmentioning
confidence: 76%
“…5). Further there is no weight loss upto 800 C. Therefore it can be concluded that physiosorbed and chemisorbed ZnBr 2 on silica surfaces is stable upto 800 C. 37…”
Section: Resultsmentioning
confidence: 76%